Brand trust: Exploring the roles of environmental, social, and governance and digital transformation - Tran, Sy Nguyen; Doan, Linh; Viet, Thuan Huynh Ngo; Nhat, Minh Vo Tran; Ha, Ngan Tong Vu (Edelweiss Applied Science and Technology, 2025)
Currently, in times of digital transformation, there has been a growing attention paid to sustainability and corporate responsibility, so ESG practices play a pivotal role in shaping brand trust, which is essential for long-term consumer loyalty and engagement. The objective of the research is to understand how ESG has impacted the brand trust of consumers under the moderating effect of digital transformation. Accordingly, using a quantitative research design, primary data was collected from 302 dairy consumers located in Vietnam through a survey and analyzed using SmartPLS software through Partial Least Squares-Structural Equation Modeling. The results indicate that the implementation of ESG practices has a positive and direct relationship with consumers' brand trust in dairy products. Specifically, the social factor has the most notably positive effect on brand trust, followed by environmental and governance factors, respectively. The results also emphasize the moderating impact of digital transformation in boosting the positive influence of environmental and governance factors on brand trust, while the relationship between the social factor and brand trust is not significantly moderated.